Physical Activity Types Among School-Aged Children During COVID-19 Pandemic in Saudi Arabia: A Cross-Sectional Study - Mshari Alghadier; Reem M. Basuodan; Afnan Gmmash; Reem A. Albesher (Life)
Background: The COVID-19 pandemic may have had long-lasting detrimental effects on children’s physical health. Previous studies have shown that children’s participation in physical activity (PA) declined during the pandemic. This study examined the effect of the COVID-19 pandemic on PA type selection and the influence of gender, number of siblings, residence type, and caregiver education level on PA. Methods: Parents of Saudi children (ages 6–9 years) were recruited through convenience sampling and completed an online survey between July and August 2020. The parent-reported survey included demographics and PA types across three time periods (pre-, during, and post-lockdown). Chi-squared tests and logistic regression with pairwise comparisons were used to analyze the differences. Results: Parents reported that children (n = 361, mean age 7.7 ± 1.1 years) selected different PA types pre-COVID-19 pandemic more often than during the COVID-19 lockdown, such as swimming (16.9% vs. 12.8%), high-intensity jumping (9.8% vs. 6.6%), cycling (12.8% vs. 9.6%), football (14.3% vs. 6.1%), running (9.3% vs. 5.5%), virtual gaming exercise (5% vs. 3.2%), and playground activity (11.3% vs. 5.8%) (p < 0.05). Additionally, PA type was shown to be influenced by gender and residence type, with girls being 55% more likely to be physically active during COVID-19 compared to boys, and participants living in houses without private yards being less physically active compared to those who lived in houses with private yards. Conclusions: Children’s gender (boy vs. girl) and residence type (with private yards vs. without private yards) affected their PA level during the COVID-19 lockdown. These findings suggest that more effort should be directed toward understanding the influence of gender and house types in the selection of PA types.